2022
DOI: 10.15251/djnb.2022.172.421
|View full text |Cite
|
Sign up to set email alerts
|

Rapid biogenic fabrication of silver nanoparticles using Ziziphus nummularia under optimised conditions and evaluation of their antimicrobial synergy

Abstract: Nanotechnology deals with the Nanoparticles having a size of 1-100 nm in one dimension used significantly concerning medical chemistry, atomic physics, and all other known fields. These particles can be prepared easily by different physical, chemical and biological approaches. But the biological approach is the most emerging approach of preparation because this method is easier than the other methods, eco-friendly and less time consuming. In this study green synthesis of silver nanoparticles (AgNPs) of Ziziphu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Kumar et al biosynthesized silver nanoparticles from roots extract of Ziziphus nummularia. The result revealed that nanoparticle possesses significant antimicrobial potential against Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, Escherichia coli, Aspergillus niger, and Candida albicans strains (Kumar et al 2022). Similar improvement was observed in another study, using synthesized nanoparticles from fruit extracts of Ziziphus nummularia, which found strong potential against gram-negative and gram-positive bacteria, fungal strain, as well as showing better hair growth (Khalil et al 2022).…”
Section: Advanced Formulation Of the Plant Genussupporting
confidence: 61%
See 1 more Smart Citation
“…Kumar et al biosynthesized silver nanoparticles from roots extract of Ziziphus nummularia. The result revealed that nanoparticle possesses significant antimicrobial potential against Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, Escherichia coli, Aspergillus niger, and Candida albicans strains (Kumar et al 2022). Similar improvement was observed in another study, using synthesized nanoparticles from fruit extracts of Ziziphus nummularia, which found strong potential against gram-negative and gram-positive bacteria, fungal strain, as well as showing better hair growth (Khalil et al 2022).…”
Section: Advanced Formulation Of the Plant Genussupporting
confidence: 61%
“…Nanotechnology is an emerging field with the application of molecular imaging, catalysis, drug discovery, and other diagnostic purposes; it involves the production of molecules with a range of 1-100 nanometers in length (Kumar et al 2022). "Green synthesis" of nanoparticles is the most fascinating technique now a day.…”
Section: Advanced Formulation Of the Plant Genusmentioning
confidence: 99%
“…The shape, size and surface area of AgNPs were studied [89]. An improvement of AFM over conventional microscopes is that it uses three-dimensional images that allow height and volume to be determined [83].…”
Section: Afmmentioning
confidence: 99%
“…The antibacterial activity of AgNPs has been studied widely with human pathogenic agents [31][32][33]. There are innumerous microbial species in nature which are acidogenic and are involved in the origination and continuation of dental diseases in humans [34][35][36]. Streptococcus is considered to be one of the most common disease-causing agents in oral diseases [37,38], especially plaque, because of its anomalous properties of fermenting sugars and synthesizing extracellular polysaccharides [39,40].…”
Section: Introductionmentioning
confidence: 99%